Upaya Guru Pendidikan Agama Islam dalam Mengatasi Dekadensi Moral Peserta Didik di SMP Al-Ma’arif NU Merauke - Kadir, Abdul; Aljauhari, Shofwan; Faisal, Faisal; Taslim, Muhammad (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2023)
Teachers make various efforts to achieve educational goals, these include efforts to overcome the moral decadence of students. This study discusses the efforts of Islamic Religious Education Teachers in overcoming the moral decadence of students. By using field research, this research begins with observation, interviews as well as documentation related to the problem being analyzed. The use of field research aims to examine and find out the efforts of Islamic Religious Education Teachers in overcoming the moral decadence of students. This research showed that the efforts made by Islamic Religious Education teachers to overcome the moral decadence of students include preventive efforts, curative efforts, and nurturing efforts. These efforts create a more conducive school situation and a more communicative relationship between all concerned sides, among students, teachers, and the parents of students. The implication of efforts to overcome moral decadence made by all sides is how the process can be adjusted to the pattern and pace, as well as the rhythm of learner development.